A qualitative examination of home and neighborhood environments for obesity prevention in rural adults - Ballard Denise; Alcantara Iris; Escoffery Cam; Kegler Michelle C; Glanz Karen (BMC, 2008)
Abstract Background The home and neighborhood environments may be important in obesity prevention by virtue of food availability, food preparation, cues and opportunities for physical activity, and family support. To date, little research has examined how home and neighborhood environments in rural communities may support or hinder healthy eating and physical activity. This paper reports characteristics of rural homes and neighborhoods related to physical activity environments, availability of healthy foods, and family support for physical activity and maintaining an ideal body weight. Methods In-depth interviews were conducted with 60 African American and White adults over 50 years of age in two rural counties in Southwest Georgia. Interviews were transcribed verbatim and coded independently by two members of the research team using standard methods of qualitative analysis. Themes were then identified and data matrices were used to identify patterns by gender or race. Results Neighborhood features that supported physical activity were plenty of land, minimal traffic and living in a safe and friendly neighborhood. The major barrier was lack of recreational facilities. The majority of participants were not physically active with their family members due to schedule conflicts and lack of time. Family member-initiated efforts to encourage physical activity met with mixed results, with refusals, procrastination, and increased activity all reported. Participants generally reported it was easy to get healthy foods, although cost barriers and the need to drive to a larger town for a supermarket with good variety were noted as obstacles. Family conversations about weight had occurred for about half of the participants, with reactions ranging from agreement about the need to lose weight to frustration. Conclusion This study suggests that successful environmental change strategies to promote physical activity and healthy eating in rural neighborhoods may differ from those used in urban neighborhoods. The findings also provide insight into the complexities of family support for physical activity and maintaining a healthy weight. Addressing socio-ecologic factors has the potential to increase healthy behaviors and decrease the prevalence of obesity among rural residents.